Peningkatan Hasil Belajar Biologi melalui Model Group Investigation di Kelas XI SMA Negeri 1 Tutuyan - Nivensia Geby Maramis; Jantje Ngangi; Anita C. C. Tengker (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
The low learning outcomes of students in Biology learning at SMA Negeri 1 Tutuyan is the background for the need for learning innovations that are able to increase active participation and conceptual understanding. This study aims to analyze the effectiveness of the Group Investigation learning model in improving student learning outcomes in Cell materials. The research used a pseudo-experiment method with a one group pretest-posttest design. The research sample amounted to 35 students from class XI Science who were selected purposefully. The instruments used were multiple-choice tests, pre-tests and post-tests of 25 questions for each test. The results showed an increase in the average score from 23.14 in the pre-test to 83.14 in the post-test. Inferential data analysis using the t-test showed a t-calculated value of 89.55, far above the t-table at a significance level of 5%. The category of student learning outcomes has also undergone significant changes, from a very low majority to a high and very high majority. The application of the Group Investigation model encourages students to be active in investigation, group discussions, and independent learning, which strengthens their collective and individual mastery of the material. These findings prove that the Group Investigation model is effective in improving learning outcomes, and can be implemented as a learning strategy in the Independent Learning Curriculum. This study contributes to the development of cooperative learning models in the context of Biology learning at the high school level, and can be replicated in other materials and levels to strengthen its effectiveness.